Performance-Based Design of Tall Timber Buildings Under Earthquake and Wind Multi-Hazard Loads: Past, Present, and Future - Tesfamariam, S. (Frontiers in Built Environment, 2022)
Rapid growth of urban population and associated environmental concerns are challenging city planners and developers to consider sustainable and cost efficient building systems. Timber-based buildings, such as sustainable system, is increasingly used. The timber buildings, however, being lighter and flexible, can be vulnerable to earthquake and wind loads. This paper gives a state of the art review on performance-based design (PBD) considerations and future direction for timber and timber-based hybrid buildings. The PBD review covered both earthquake and wind loads, and multi-hazard design consideration. The review also provided 1) current practice and future direction in the consideration of hazard, response and loss assessment within the MH PBD, 2) damping and energy dissipation devices, 3) optimization under uncertainty and 4) future of surrogate and multi-fidelity modelling in PBD.